Intravenous thrombolysis in patients with ischemic stroke aged ≥90 years: a cohort study from the TRISP Collaboration - Altersberger, Valerian L.; Rusche, Norman; Martinez-Majander, Nicolas; Hametner, Christian; Scheitz, Jan F.; Henon, Hilde; Dell’Acqua, Maria Luisa; Strambo, Davide; Stolp, Jeffrey; Heldner, Mirjam R.; Grisendi, Ilaria; Jovanovic, Dejana R.; et al. (Stroke, 2022)
Background: - - The probability to receive intravenous thrombolysis (IVT) for treatment of acute ischemic stroke declines with increasing age and is consequently the lowest in very elderly patients. Safety concerns likely influence individual IVT treatment decisions. Using data from a large IVT registry, we aimed to provide more evidence on safety of IVT in the very elderly. - - Methods: - - In this prospective multicenter study from the TRISP (Thrombolysis in Ischemic Stroke Patients) registry, we compared patients ≥90 years with those <90 years using symptomatic intracranial hemorrhage (ECASS [European Cooperative Acute Stroke Study]-II criteria), death, and poor functional outcome in survivors (modified Rankin Scale score 3-5 for patients with prestroke modified Rankin Scale score ≤2 and modified Rankin Scale score 4-5 for patients prestroke modified Rankin Scale ≥3) at 3 months as outcomes. We calculated adjusted odds ratio with 95% CI using logistic regression models. - - Results: - - Of 16 974 eligible patients, 976 (5.7%) were ≥90 years. Patients ≥90 years had higher median National Institutes of Health Stroke Scale on admission (12 versus 8) and were more often dependent prior to the index stroke (prestroke modified Rankin Scale score of ≥3; 45.2% versus 7.4%). Occurrence of symptomatic intracranial hemorrhage (5.7% versus 4.4%, odds ratioadjusted 1.14 [0.83-1.57]) did not differ significantly between both groups. However, the probability of death (odds ratioadjusted 3.77 [3.14-4.53]) and poor functional outcome (odds ratioadjusted 2.63 [2.13-3.25]) was higher in patients aged ≥90 years. Results for the sample of centenarians (n=21) were similar. - - Conclusions: - - The probability of symptomatic intracranial hemorrhage after IVT in very elderly patients with stroke did not exceed that of their younger counterparts. The higher probability of death and poor functional outcome during follow-up in the very elderly seems not to be related to IVT treatment. Very high age itself should not be a reason to withhold IVT.